2024
DOI: 10.35848/1882-0786/ad15f3
|View full text |Cite
|
Sign up to set email alerts
|

Rutile-type Ge x Sn1−x O2 alloy layers lattice-matched to TiO2 substrates for device applications

Hitoshi Takane,
Takayoshi Oshima,
Takayuki Harada
et al.

Abstract: We report the characterization and application of mist-CVD-grown rutile-structured Ge x Sn1−x O2 (x = ∼0.53) films lattice-matched to isostructural TiO2(001) substrates. The grown surface was flat throughout the growth owing to the lattice-matching epitaxy. Additionally, the film was single-crystalline without misoriented domains and TEM-detectable threading dislocations due to the coherent heterointerface. Using the Ge0.49Sn0.51O2 film with a carrier de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…1) Recently, it was also reported that r-Ge x Sn 1−x O 2 films could be grown coherently on r-TiO 2 substrates without misoriented domains and TEMdetectable threading dislocations in the films. 14) The quality of the coherent films is high enough to fabricate Schottky barrier diodes (SBDs) with high rectification ratios, demonstrating the potential of r-Ge x Sn 1−x O 2 alloys as practical power semiconductors. 14) At present, however, power-electronic applications of r-GeO 2 , r-SnO 2 , and r-Ge x Sn 1−x O 2 alloy have been limited due to the difficulty in doping control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) Recently, it was also reported that r-Ge x Sn 1−x O 2 films could be grown coherently on r-TiO 2 substrates without misoriented domains and TEMdetectable threading dislocations in the films. 14) The quality of the coherent films is high enough to fabricate Schottky barrier diodes (SBDs) with high rectification ratios, demonstrating the potential of r-Ge x Sn 1−x O 2 alloys as practical power semiconductors. 14) At present, however, power-electronic applications of r-GeO 2 , r-SnO 2 , and r-Ge x Sn 1−x O 2 alloy have been limited due to the difficulty in doping control.…”
mentioning
confidence: 99%
“…14) The quality of the coherent films is high enough to fabricate Schottky barrier diodes (SBDs) with high rectification ratios, demonstrating the potential of r-Ge x Sn 1−x O 2 alloys as practical power semiconductors. 14) At present, however, power-electronic applications of r-GeO 2 , r-SnO 2 , and r-Ge x Sn 1−x O 2 alloy have been limited due to the difficulty in doping control. It is well known that several n-type oxides, i.e.…”
mentioning
confidence: 99%